Effects of L-arginine pre-treatment in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced Parkinson’s diseases in Balb/c mice - Hami, Javad (Iran J Neurol, 2015)
Background: Parkinson’s disease (PD) is a common neurodegenerative disease resulting from the degeneration of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNc). Increasing evidence demonstrated that mice treated intranasally with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) suffered impairments in motor functions associated with disruption of DA neurons in SNc conceivably analogous to those observed in PD. L-arginine has been proposed as a novel neuroprotective agent that plays protective roles in several models of neuronal cellular damage. This study aimed to evaluate the effects of L-arginine on the numerical density of dark neurons (DNs) in the SNc of Balb/c mice subjected to MPTP administration. Methods: In the present study, we demonstrated that repeated treatment with L-arginine (300 mg/kg, i.p.) during 7 consecutive days attenuated the production of DNs in SNc of adult male Balb/c mice infused with a single intranasal administration of MPTP (1 mg/nostril). Results: Pre-treatment with L-arginine significantly decreased the numerical density of DNs in SNc of mice 21 days after intranasal MPTP administration. Conclusion: This investigation provides new insights in experimental models of PD, indicating that L-arginine represents a potential neuroprotective agent for the prevention of DA neuron degeneration in SNc observed in PD patients.